2023
DOI: 10.1021/acsomega.3c02418
|View full text |Cite
|
Sign up to set email alerts
|

Biocompatible Drug Delivery System Based on a MOF Platform for a Sustained and Controlled Release of the Poorly Soluble Drug Norfloxacin

Preety Yadav,
Sarita Kumari,
Anand Yadav
et al.

Abstract: Norfloxacin (NFX), an important antibacterial fluoroquinolone, is a class IV drug according to the biopharmaceutics classification system (BCS) and has low solubility and permeability issues. Such poor physicochemical properties of drug molecules lead to poor delivery and are of serious concern to the pharmaceutical industry for clinical development. We present here a conceptually new approach to deliver NFX, by loading the drug molecule on the porous platform of a biocompatible metal–organic framework (MOF), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…For example, Parsaei et al 14 successfully prepared a simple and economical MOF-801 using ZrCl 4 and fumaric acid, and used this for the controlled release of the anticancer drug 5-Fu, significantly improving the therapeutic effect of the drug. Yadav et al 15 designed and reported an iron-MOF material, NFX@MIL-100(Fe), which was used for the delivery of norfloxacin (NFX) with high loading (∼20 wt%) and expected sustained release effect. However, although numerous MOFs have been reported and extensively studied, there are insufficient practical applications related to biomedicine applications.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Parsaei et al 14 successfully prepared a simple and economical MOF-801 using ZrCl 4 and fumaric acid, and used this for the controlled release of the anticancer drug 5-Fu, significantly improving the therapeutic effect of the drug. Yadav et al 15 designed and reported an iron-MOF material, NFX@MIL-100(Fe), which was used for the delivery of norfloxacin (NFX) with high loading (∼20 wt%) and expected sustained release effect. However, although numerous MOFs have been reported and extensively studied, there are insufficient practical applications related to biomedicine applications.…”
Section: Introductionmentioning
confidence: 99%
“…Solventless reaction conditions provide many benefits, like a significant reduction in the reactor size, less energy consumption, shortened reaction times, and high yield . Popular choices of heterogeneous catalysts for the said reactions are metal–organic frameworks (MOFs), a novel class of materials that are constructed by metal ions/clusters with organic molecules as ligands. , MOFs have found applications in areas such as drug delivery, gas storage, gas separation, sensing, catalysis, etc. Heterogeneous catalysis based on MOFs has grown up over the years and created interest to materials scientists due to its remarkable properties such as high porosity, tunable pores, functionalizable pore walls, and relatively simple separation. , MOFs with well-defined pores or channels are useful for their high activity in the catalytic process.…”
Section: Introductionmentioning
confidence: 99%
“…MOFs can be developed using synthetic and natural compounds, employing chemical and physical approaches [16,17]. These MOFs can be endowed with different chemical and physical properties and evaluated for targeted drug delivery in various diseases at the subcellular level [18,19].…”
Section: Introductionmentioning
confidence: 99%